Isolasi dan Identifikasi Fungi Mikoriza Arbuskular (Fma) secara Mikroskopis pada Rhizosfer Tanaman Jeruk (Citrus sp.) di Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - SUAMBA, I WAYAN; WIRAWAN, I GEDE PUTU; ADIARTAYASA, WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Isolation and Identification of Arbuscular Mycorrhizal Fungi (AMF) by Microscopic (AMF) in Rhizosphere of Citrus Plant ( Citrus sp.) in Kerta Village, Payangan District, Gianyar Regency Arbuscular Mycorrhizal Fungi (AMF) is a group of organisms from fungi that describes a form of mutualism between symbiotic fungi and plant roots. AMF has great potential as a biological fertilizer because the microorganism which has a very important role in facilitating the absorption of nutrients in the soil to increase plant growth, in addition AMF also function as a biological barrier against pathogen that infect the roots, increasing the availability of water for plants to grow and improve hormone boosters. The purpose of the study was to determine the types of AMF that exist in the rhizosphere of citrus plant and determine the presence of infection by the AMF in the citrus plant roots in the  village of Kerta. The results of the isolation and identification of AMF spores in the rhizosphere of citrus plants in the village of Kerta found 14 different types of AMF spores. This study found 7 type of Glomus , 5 types of Gigaspora and 2 types of Acaulospora . Those types were determined by using the characteristic of their spores. Observations on root finding that the AMF  infection in the form vesicles and arbuscular structures. Keywords : Arbuscular Mycorrhizal Fungi, Glomus, Gigaspora, Acaulospora, Vesicles and Arbuscular .
Keywords: Arbuscular Mycorrhizal Fungi; Glomus; Gigaspora; Acaulospora; Vesicles and Arbuscular